2013
DOI: 10.1002/wcc.236
|View full text |Cite
|
Sign up to set email alerts
|

Climate change regional review: Russia

Abstract: With climate change, an increasingly important focus of scientific and policy discourse, the Russian government has aimed to position the country as one of the leaders of the global process for addressing climate change. This article reviews a breadth of literature to analyze the politico-economic situation in Russia with regard to international climate change negotiations, related domestic policies, societal attitudes, and climatic change impacts on Russia's territory. The analysis demonstrates how Russia has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The warming of permafrost in Russia has the potential to influence global climate change because the thawing of frozen soil releases soil organic carbon [83]. At longer timescales in the past, Russia's winter became warmer, and the greenhouse gas effect has been considered as an important factor for this warming [84]. Based on the results of the AIRS CO 2 data, CO 2 continues to increase globally.…”
Section: Potential Climatic Variables Associated With Lst Trendsmentioning
confidence: 99%
“…The warming of permafrost in Russia has the potential to influence global climate change because the thawing of frozen soil releases soil organic carbon [83]. At longer timescales in the past, Russia's winter became warmer, and the greenhouse gas effect has been considered as an important factor for this warming [84]. Based on the results of the AIRS CO 2 data, CO 2 continues to increase globally.…”
Section: Potential Climatic Variables Associated With Lst Trendsmentioning
confidence: 99%
“…With continuing and accelerating climate change, there is a risk that the boreal forest may even cross a tipping point and shift to an alternative state (Chapin et al, 2005;Lenton et al, 2008;Scheffer et al, 2012). Other prospective impacts of future climate change on forest ecosystems in Russia, as documented in Russian-language literature, have been reviewed by Sharmina et al (2013). They found that the key anticipated impacts are potential shifts of vegetation zones, more frequent and intensive wildfires, and increased plant productivity through CO 2 fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Russia has repeatedly reaffirmed its commitment to 2 C in subsequent international agreements, including the Group of Eight Camp David Declaration in 2012 [19]. In the absence of ambitious domestic mitigation policies [20] and for the purpose of this paper, the Russian government's commitment to this quantitative framing of climate change is taken at face value and in good faith.…”
Section: Introductionmentioning
confidence: 91%